2020
DOI: 10.1111/bjh.16737
|View full text |Cite
|
Sign up to set email alerts
|

Survival of very elderly patients with diffuse large B‐cell lymphoma according to treatment intensity in the immunochemotherapy era: a Swedish Lymphoma Register study

Abstract: Diffuse large B-cell lymphoma (DLBCL) incidence rises with increasing age. Rituximab-anthracycline-based regimens offer a potential cure but also risks of adverse events, especially in the elderly. Using Swedish registers, we conducted a nationwide, population-based study of DLBCL in the very elderly. We obtained information on clinical characteristics, residence, comorbidity, therapy and survival for the 1194 patients aged ≥80 years diagnosed in Sweden 2007-2014. To address selection bias, we also investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the study by FIL, 19,47 unfit patients had similar OS following full-dose R-CHOP ($70%) and attenuated R-CHOP (,70%) but poorer survival following an anthracycline-free regimen, although the results were not adjusted for possible confounders. Registry-based and smaller retrospective studies 8,[31][32][33]50 report better outcomes with an anthracycline-containing regimen, also for older patients and for patients with comorbidity. None of these studies stratified their analyses according to frailty status.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by FIL, 19,47 unfit patients had similar OS following full-dose R-CHOP ($70%) and attenuated R-CHOP (,70%) but poorer survival following an anthracycline-free regimen, although the results were not adjusted for possible confounders. Registry-based and smaller retrospective studies 8,[31][32][33]50 report better outcomes with an anthracycline-containing regimen, also for older patients and for patients with comorbidity. None of these studies stratified their analyses according to frailty status.…”
Section: Discussionmentioning
confidence: 99%
“…In particular there was a decrease in PFS with less intensive treatments 25,29,36 . These results were recently confirmed by a large retrospective study by Sonnevi et al 47 In total, 1195 patients over 80 years old with DLBCL had an OS at 2 years of 54% in the standard curative treatment group versus 26% in the less intensive treatment group ( p < .005).…”
Section: Discussionmentioning
confidence: 67%
“…Chelsea et al explored incorporating consolidative radiation therapy (RT) to reduce overall chemotherapy drug exposure, they found age older than 80 years who with early-stage patients, 3 to 4 cycles of chemotherapy followed by RT of disease free survival (DFS), PFS, OS (P=0.78, P=0.654, P=0.852) were equivalent to chemotherapy alone and was associated with less toxic reaction, which suggested that RT following short chemotherapy may be a better choice for some earlystage elderly patients who could not tolerate standard course of chemotherapy [9]. A study from the Swedish Lymphoma Register showed that very elderly patients seem to bene t from rituximabanthracycline-based treatment [10]. However, most of very elderly patients are associated with an increasing risk of coronary artery diseases, the use of potentially cardiotoxic drugs such as anthracyclinebased chemotherapy may not tolerate.…”
Section: Case Presentationmentioning
confidence: 99%